Effect of Supplementation of Probiotics in Paddy Straw Based Complete Ration on Performance and Economics of Feeding in Lambs - Sheikh, G. G.; Ganai, A. M.; Ahmad, H. A.; Afzal, Y.; Amin, Umar; Ahmad, Mudasir (Indian Journal of Animal Nutrition, 2017)
Twelve male Corriedale lambs (3-4 months old) were divided in 2 groups of 6 lambs each to study the effect of addition of probiotics in paddy straw based complete feeds on growth and nutrient utilisation. A complete feed was prepared using paddy straw and concentrate mixture in 50: 50 ratio. In probiotics group,probiotics (Saccharomyces cerevisiae 2Ã—1010 cfu/g + Lactobacillus acidophilus 6Ã—109 cfu/g) was given @ 3% of dietary DM. The values for DMI, gain in body weight, body length, chest girth, feed conversion ratio, digestibility of nutrients (DM, OM, CP, CF, NFE, NDF, ADF, hemicellulose and cellulose), balances of N, Ca andP, contents of DCP, TDN, DE and ME in the ratiom were higher (P